2013
DOI: 10.1038/onc.2013.470
|View full text |Cite
|
Sign up to set email alerts
|

E2F1 drives chemotherapeutic drug resistance via ABCG2

Abstract: Multidrug resistance is a major barrier against successful chemotherapy, and this has been shown in vitro to be often caused by ATP-binding cassette (ABC) transporters. These transporters are frequently overexpressed in human cancers and confer an adverse prognosis in many common malignancies. The genetic factors, however, that initiate their expression in cancer are largely unknown. Here we report that the major multidrug transporter ABCG2 (BCRP/MXR) is directly and specifically activated by the transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…E2F1 plays an important role in regulating development, differentiation, proliferation, cellular signal transduction, and apoptosis (9)(10)(11)(12). Certain studies reported that E2F1 disrupts a range of pathways in numerous cancers and is closely correlated with clinical parameters (13)(14)(15). We had also previously identified that E2F1 is upregulated in ccRCC progression (16).…”
Section: Introductionmentioning
confidence: 99%
“…E2F1 plays an important role in regulating development, differentiation, proliferation, cellular signal transduction, and apoptosis (9)(10)(11)(12). Certain studies reported that E2F1 disrupts a range of pathways in numerous cancers and is closely correlated with clinical parameters (13)(14)(15). We had also previously identified that E2F1 is upregulated in ccRCC progression (16).…”
Section: Introductionmentioning
confidence: 99%
“…Yoshihara et al also showed that28 p21 and BAX expressions could be increased and the apoptosis caused by ADR also enhanced by decreasing intracellular E2F1 expression. Rosenfeldt et al found that E2F1 could increase the resistance to chemotherapeutic drugs by regulating ABCG2 expression level in the cells 29. Altogether, these results indicated that the high expression of E2F was one of the factors improving tumor drug resistance and could be a potential target for regulating tumor cells’ drug resistance.…”
Section: Discussionmentioning
confidence: 95%
“…We suppose that the expression and activity of BCRP in cBCRP cells is not mediated through Akt signalling. a recent study identified the transcription factor e2F1, implicated in various cellular functions, as another possible activator of BCRP expression in various human lung cancer cell lines (23). Moreover, Rosenfeld et al (23) revealed that the E2F-BCRP axis suppresses chemotherapy-induced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…a recent study identified the transcription factor e2F1, implicated in various cellular functions, as another possible activator of BCRP expression in various human lung cancer cell lines (23). Moreover, Rosenfeld et al (23) revealed that the E2F-BCRP axis suppresses chemotherapy-induced cell death. Another important fact corresponding with our results is the attenuation of this resistance via BCRP inhibition.…”
Section: Discussionmentioning
confidence: 99%